PSYCHOLOGICAL WELL-BEING PESERTA DIDIK SEKOLAH DASAR DAN IMPLIKASINYA TERHADAP PROGRAM BIMBINGAN DAN KONSELING - Kristina Betty Artati; Herdi Herdi (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
Purpose: The aim of this study is  to describe the profile of Psychological well-being of grade 6 students and as a basic arrangements of guidance and counseling program in elementary schools. Method: The technique used for this study is a descriptive technique with a quantitative approach, collecting data using the SCWBS instrument. The subjects for this study were 80 students of grade VI from a private school in Lampung with an age range of 11-12 years. Conclusion;The results in this study obtained 31. 3% of students with the psychological well-being in the high category, 56.3% in the medium category and 12.5% in the low category. Based on the analysis of the data, the psychological well-being of grade 6 in one of the private elementary school Lampung that using SCWBS psychological well-being instrument is in the moderate category and forms the basis for preparing a program in schools with a mindfulness approach to improve students' psychological well-being